2019
DOI: 10.1016/j.invent.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of a social support platform ‘Inlife’ for caregivers of people with dementia

Abstract: IntroductionInformal caregivers of persons with dementia have an increased risk of facing social isolation. Online social media interventions might offer a new opportunity to increase access to social support. An online social support platform, ‘Inlife’, was developed and launched in the Netherlands to enhance social support, positive interactions and information sharing in informal support networks.ObjectiveA process evaluation was performed to evaluate the internal and external validity of the Inlife interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 24 publications
4
62
0
1
Order By: Relevance
“…Se reportan estudios con resultados similares a los obtenidos en esta investigación (35,36), implementando TIC como plataformas virtuales y teleconferencias que procuran brindar educación al cuidador sobre la enfermedad, redes de apoyo social e interacción con otros cuidadores, con el fin de aminorar la carga de cuidado, lo que evidencia baja adherencia de los cuidadores a las TIC, sin cambios significativos sobre la variable de percepción de carga.…”
Section: Discussionunclassified
“…Se reportan estudios con resultados similares a los obtenidos en esta investigación (35,36), implementando TIC como plataformas virtuales y teleconferencias que procuran brindar educación al cuidador sobre la enfermedad, redes de apoyo social e interacción con otros cuidadores, con el fin de aminorar la carga de cuidado, lo que evidencia baja adherencia de los cuidadores a las TIC, sin cambios significativos sobre la variable de percepción de carga.…”
Section: Discussionunclassified
“…Regarding the results of the internet search and the survey responses, the findings indicated that, 3/5 of the authors of the still-available interventions took part in the survey, versus 3/7 of the authors of the discontinued interventions. Based on the available online information and the responses received from the authors, it could be deduced that, of the five still-operating interventions, two were exclusively available through participating in a trial 29,31 , one was only available to select clinical staff previously associated with the research project 32 , and two were freely available online 28,30 . The most commonly reported facilitator (mentioned in four out of six responses), developing a commercialisation and/or business plan, did not appear to be a guarantee of success.…”
Section: Integrated Resultsmentioning
confidence: 99%
“…Instead, there is a marked focus on effectiveness research. A frequently used framework that guides much of this intervention effectiveness research is the Medical Research Council's (MRC) framework for complex interventions 29 . It has been used in a variety of contexts to develop and evaluate complex interventions, including interventions in dementia care 30,31 .…”
Section: Psychosocial Interventions For Dementiamentioning
confidence: 99%
See 2 more Smart Citations